KAJIAN TERHADAP PROSES PENYELESAIAN PERKARA KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG DI PENGADILAN NIAGA JAKARTA PUSAT KAJIAN TERHADAP PROSES PENYELESAIAN PERKARA KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG DI PENGADILAN NIAGA JAKARTA P - Ratnawati, Theresia Endang (Jurnal Dinamika Hukum, 2009)
Law No.4 Year 1998 is not yet accomodate the importance of corporate in the world. To soving the constraint in applying of Law No. 4 Year 1998, the government have released Law No. 37 Year 2004 that concerning Bankrupt and Postponement of Obligation To Pay Debt in the place of Law No. 4 Year 1998. in the other side, the released of Law No.37 Year 2004 not yet earned the enthusiasm of the creditors to go through bankrupt process to finishing loan that stuck from [all] his debitors. Pursuant to the research, it can be concluded that amount of the cases of bankrupt is influenced by subtantion of law that arranging bankrupt, institute performance/ commisioned functionary that handle bankrupt case and  asset of recovery of the bankrupt process. Result of lowness asset recovery and process of solving the case of bankrupt which is relative long will be degraded the enthusiasm of the creditor to finish the receivable of passing bankrupt process.Kata Kunci: Kepailitan, Asset Recovery